(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
At present, the teacher in hearing and language consolidates as a teaching specialty, and his markedly itinerant character in schools is noteworthy. The present study has tried to make a qualitative approach to the core of the evaluation process, both diagnostic and curricular, which develops this profile of specialist teacher. It has been tried to glimpse the character that said professionals grant to the evaluation in their performance and the implications in order to promote an educational sense to it. Among the conclusions, we can see a marked individual-diagnostic accent in this intervention, providing as a conclusion what would constitute the lines of action to enhance a collaborative-training profile in the development of student assessment by these professionals.